2017
DOI: 10.12968/jpar.2017.9.8.348
|View full text |Cite
|
Sign up to set email alerts
|

Development of clinical and inter-personal skills to support people living with dementia

Abstract: There is a lack of understanding on how paramedic students develop their knowledge, skills and attitudes to support people living with dementia and their families in the community. This qualitative study used focus groups to explore paramedic students' perspectives. 1st and 3rd year paramedic students were recruited from two ambulance service providers in the South of England. Data were collected during 2017 and four themes emerged: 1) impact of dementia on all concerned 2) challenges of communicating with peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…In part, this problem can be sensed in research stressing that ACs might lack awareness of the older patients' physical and mental abilities as they are often disregarded because patients do not convey their desires (Boltz et al, 2013). A study indicated that the capability to communicate and understand the patient as well as to obtain consent can be difficult (Brooke & Stiell, 2017). It can be assumed that these factors influence co-creation in the relationship between the older patient and the ACs.…”
Section: 6mentioning
confidence: 99%
“…In part, this problem can be sensed in research stressing that ACs might lack awareness of the older patients' physical and mental abilities as they are often disregarded because patients do not convey their desires (Boltz et al, 2013). A study indicated that the capability to communicate and understand the patient as well as to obtain consent can be difficult (Brooke & Stiell, 2017). It can be assumed that these factors influence co-creation in the relationship between the older patient and the ACs.…”
Section: 6mentioning
confidence: 99%
“…The preliminary findings discussed in the current article indicate a promising effect on preparing undergraduate paramedic students for future practice. Brooke and Stiell (2017) highlight a lack of research involving paramedic education around the care of people with dementia and their families. Findings of this research could contribute to an undergraduate paramedic education framework that improves emergency dementia care.…”
Section: Resultsmentioning
confidence: 99%
“…Making the personal and physical environment more familiar combats disorientation and lessens the fear and anxiety for people with dementia [ 60 , 63 , 68 ]. This can be helped by (i) limiting staff rotations across wards [ 37 ], (ii) fostering an environment that encourages staff, people with dementia and carers to get to know each other [ 16 , 66 , 67 , 69 ], (iii) minimising moving people with dementia within and between wards [ 29 , 58 ] and (iv) encouraging families to personalise the space [ 68 ]. Orientation is particularly important for people with dementia arriving on the ward but also throughout their stay.…”
Section: Dementia In the Acute Care Settingmentioning
confidence: 99%